The utilization of specialized healthcare services among frail older adults in the Helsinki Birth Cohort Study - Jenni N. Ikonen; Johan G. Eriksson; Minna K. Salonen; Eero Kajantie; Otso Arponen; Markus J. Haapanen (Annals of Medicine)
Background The association between frailty and specialized healthcare utilization is not well studied. We, therefore, examined the utilization of specialized healthcare services among frail Finnish older adults.Methods A sub-sample of 1060 participants of the Helsinki Birth Cohort Study were followed prospectively for specialized healthcare utilization from nationwide registers between the years 2013 and 2017. The participants’ frailty status was assessed according to Fried’s criteria at a mean age of 71.0 (2.7 SD) years between the years 2011 and 2013. A negative binomial regression model was used to examine the association between frailty and the total number of visits, emergency visits, outpatient appointments separating the first outpatient appointments and the follow-up appointments, inpatient care including elective and non-elective hospital admissions and the total number of hospital days. We also calculated average length of stay (ALOS) and used the Kruskal–Wallis test to examine the differences between the groups.Results After adjusting for covariates, frailty was significantly associated with the number of specialized healthcare visits (IRR 1.50, 95% CI = 1.04–2.15) and all subgroups of visits apart from follow-up outpatient appointments. Frailty was particularly strongly associated with the number of hospital days (IRR 5.24, 95% CI = 2.35–11.7) and notably with emergency visits (IRR = 2.26, 95% CI = 1.45–3.51) and hospital admissions (IRR 2.23, 95% CI = 1.39–3.56). Frail older adults had also higher ALOS compared to non-frail participants (p = .009).Conclusions Frailty increases the use of most specialized healthcare services. Preventative interventions against frailty are needed to decrease the burden on specialized healthcare systems.KEY MESSAGEFrailty is associated with the utilization of most specialized healthcare services, the most expensive part of the healthcare in most high-income countries.The association of frailty with inpatient care is particularly strong.Preventative interventions against frailty are needed to decrease the burden on specialized healthcare systems.